Life Cycle Stages and Debt Maturity in Brazilian Listed Companies - Leonardo Valter Bregonci; Vagner Antônio Marques; Bruno Magri Magalhães Pinto; Hudson Fernandes Amaral (BBR: Brazilian Business Review)
We have analyzed the association between firms' life cycle stages (LCSs) and their debt maturity (DM). This paper deepens the discussion on capital structure from the perspective of the LCSs' dynamic effect associated with DM. The sample was composed by secondary data from 370 (non-financial) Brazilian listed companies in the period from 2010 to 2019, gathered quarterly. The data were analyzed through descriptive statistics, tests of differences between means and regression analysis from panel data. The results showed that the DM presents no association with LCS, following an inverted U-shape. It has been observed that the maturity stage had a positive effect on the DM, however, as companies move towards the shake-out and decline stages, DM experiences successive reductions. The findings are relevant for providing insights for future research. In addition, they have the potential to contribute to managers, board members, credit committees, capital providers in general, risk management process, and resource allocation.